Stromally Derived Lysyl Oxidase Promotes Metastasis of Transforming Growth Factor-β Deficient Mouse Mammary Carcinomas - Pickup, Michael W. (2013)
The tumor stromal environment can dictate many aspects of tumor progression. A complete understanding of factors driving stromal activation and their role in tumor metastasis is critical to furthering research with the goal of therapeutic intervention. Polyoma middle T-induced mammary carcinomas lacking the type II TGF-ß receptor (PyMT(mgko)) are highly metastatic compared to control PyMT-induced carcinomas (PyMT(fl/fl)). We hypothesized that the PyMT(mgko) activated stroma interacts with carcinoma cells to promote invasion and metastasis. We show that the extracellular matrix associated with PyMT(mgko) tumors is stiffer, has more fibrillar collagen, and increased expression of the collagen crosslinking enzyme lysyl oxidase (LOX) compared to PyMT(fl/fl) mammary carcinomas. Inhibition of LOX activity in PyMT(mgko) mice had no effect on tumor latency and size, but significantly decreased tumor metastasis through inhibition of tumor cell intravasation. This phenotype was associated with a decrease in keratin 14 positive myoepithelial cells in PyMT(mgko) tumors following LOX inhibition as well as a decrease in focal adhesion formation. Interestingly, the primary source of LOX was found to be activated fibroblasts. LOX expression in these fibroblasts can be driven by myeloid cell-derived TGF-ß, which is significantly linked to human breast cancer. Overall, stromal expansion in PyMT(mgko) tumors is likely caused through the modulation of immune cell infiltrates to promote fibroblast activation. This feeds back to the epithelium to promote metastasis by modulating phenotypic characteristics of basal cells. Our data indicate that epithelial induction of microenvironmental changes can play a significant role in tumorigenesis and attenuating these changes can inhibit metastasis.